METRONIDAZOLE EFFICIENCY IN PREPARATIONS FOR CAESAREAN SECTION IN WOMEN WITH BACTERIAL VAGINOSIS - A. A. Badaeva; V. G. Volkov (Акушерство, гинекология и репродукция, 2016)
Bacterial vaginosis is a serious risk factor of postnatal infectious complications development. It was established that there were significantly fewer cases of fever, leukocytosis and uterine disorders development during postnatal period among women with bacterial vaginosis treated by metronidazole in a dose of 500 mg twice a day within 10 days, than among untreated women